Wear-resistant and chemical corrosion-resistant castable and preparation method thereof
By adding modified waste bag fibers and modified titanate whiskers to the refractory castable, the interface bonding and filling structure between the particles is improved, and the problem of existing refractory castables being eroded by chemical substances in the furnace is solved, and the effect of significantly improving wear resistance and chemical corrosion resistance is achieved.
Patent Information
- Application Number
- CN202411935393.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-28
AI Technical Summary
The existing refractory castables are eroded by chemical substances in the furnace, resulting in a decrease in wear and corrosion resistance.
A wear-resistant and chemical corrosion-resistant castable material is adopted, and its formulation includes powder, modified waste bag fiber, modified potassium titanate whiskers, bonding agents and additives. By improving the interface bonding and filling structure between particles, the overall strength and corrosion resistance of the material are enhanced.
It significantly improves the wear resistance and chemical corrosion resistance of the castable material and extends the service life of the material.
Smart Images

Figure CN119707464A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of castables, and in particular to a wear-resistant and chemical-corrosion-resistant castable and a preparation method thereof. Background Art
[0002] Refractory castables are a mixture of refractory aggregates, powders and binders. After adding water or other liquids, they are suitable for construction by pouring and vibration methods. They can also be prefabricated into prefabricated parts with specified shapes and sizes for the construction of industrial furnace linings. In order to improve the physical and chemical properties and construction performance of refractory castables, appropriate amounts of additives are often added, such as plasticizers, dispersants, accelerators, retarders, expanders, debonders and gelling agents, etc.
[0003] In the furnace, refractory castables will come into contact with various chemicals, such as gases and slag produced by fuel combustion. Acidic gases and alkali metals in these chemicals will chemically corrode the castables, destroy their internal structure, and reduce their wear resistance and corrosion resistance.
[0004] In order to solve the above problems, the present invention decides to design a wear-resistant and chemical-corrosion-resistant castable and a preparation method thereof. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a wear-resistant and chemical-corrosion-resistant castable and a preparation method thereof.
[0006] A wear-resistant and chemical-corrosion-resistant casting material, comprising, by mass percentage:
[0007] Powder: 20-25%;
[0008] Modified waste bag fiber: 1-2%;
[0009] Modified potassium titanate whiskers: 0.5-1%;
[0010] Binder: 4-6%;
[0011] Additives: 1-3%;
[0012] Aggregate: remainder;
[0013] The aggregate is composed of corundum and spinel in a mass ratio of 2.5 to 5:1;
[0014] The powder material is composed of silicon carbide micropowder and nano-alumina in a mass ratio of 1:2-4.
[0015] Furthermore, the particle sizes of the corundum include 3-5mm, 1-3mm, and ≤1mm, and the mass ratio of the three particle sizes is 1.5-2:1:2; the particle sizes of the spinel include 0.08-1mm, 0.008-0.08mm, and ≤0.008mm, and the mass ratio of the three particle sizes is 4-5:3:3.
[0016] Description: The appropriate particle size ratio can improve the interfacial bonding between corundum and spinel particles and between them and the matrix. The smaller spinel particles can better adhere to the surface of the corundum particles, increase the contact area, and improve the bonding strength. At the same time, this good interfacial bonding also helps to transfer and disperse stress, further enhancing the overall strength of the castable. The smaller spinel and corundum particles can fill the pores between the large particles to form a denser microstructure, which acts as a physical barrier to resist the invasion of chemical corrosive substances. It is difficult for the corrosive medium to penetrate into the castable through this tightly packed particle structure, thereby reducing the erosion and damage to the castable.
[0017] Furthermore, the particle size of the silicon carbide powder is ≤0.01 mm; and the particle size of the nano-alumina is ≤5 nm.
[0018] Description: Silicon carbide powder with a particle size of ≤0.01mm can be filled into the tiny gaps between castable aggregates to make the structure of the castable denser. During the wear process, this dense structure can reduce the shedding and displacement of particles and enhance the overall wear resistance; nano-alumina particles can form a hard wear-resistant network structure on the surface to prevent further development of wear.
[0019] Furthermore, the preparation method of the modified waste bag fiber is as follows:
[0020] First, the waste bags are cleaned, dried and crushed to obtain bag fibers with a length of 3 to 6 mm and a diameter of 15 to 20 um;
[0021] The bag fiber is vacuum impregnated in a sucrose solution with a mass fraction of 15-20% at a mass ratio of 1:20-30 for 3-4 hours, and the vacuum degree is 3×10 -4 ~4×10 -4 Pa; then the vacuum impregnated bag fiber is subjected to decoupled plasma nitridation treatment, wherein the radio frequency power of the decoupled plasma nitridation treatment is 2800-3000W, the nitrogen flow rate is 230-240mL / min, and the treatment time is 1-2min; finally, the bag fiber after the decoupled plasma nitridation treatment is vacuum impregnated in a sucrose solution with a mass fraction of 25-30% at a mass ratio of 1:5-10 for 0.5-1h, and the vacuum degree is 1×10 -4 ~2×10 -4Pa; obtain modified waste cloth bag fiber.
[0022] Description: After the first sucrose solution impregnation modification, sucrose molecules will be adsorbed on the surface of the bag fiber. The subsequent decoupled plasma nitriding treatment forms a hard nitride layer on the surface of the bag fiber. This nitride layer has high hardness and wear resistance, and can effectively resist external friction and wear. The sucrose molecules will undergo carbonization and other reactions to form a carbon layer with a certain roughness and activity on the fiber surface. When the second low-pressure and high-concentration sucrose solution impregnation modification is carried out, the new sucrose molecules will interact with the carbon layer formed for the first time, further increasing the active sites and roughness of the fiber surface; to a certain extent, the toughness and wear resistance of the bag fiber are improved, making it not easy to be worn and broken in the castable.
[0023] Furthermore, the additive is zirconium oxide.
[0024] Description: Zirconia has high strength and toughness. As an additive, it can significantly improve the strength of the material, especially in high temperature environments. Zirconia has good corrosion resistance and wear resistance, which can effectively extend the life of the material.
[0025] Furthermore, the binder is pure calcium aluminate cement.
[0026] Description: Castables bonded with pure calcium aluminate cement have good demoulding strength after curing at different temperatures and have high stability under high temperature conditions.
[0027] A method for preparing a wear-resistant and chemical-corrosion-resistant castable as described in any one of the above, comprising the following steps:
[0028] S1, corundum with a particle size of 3 to 5 mm and ≤ 1 mm, spinel with a particle size of 0.08 to 1 mm and 0.008 to 0.08 mm, 60 to 70 wt% of powder, modified waste bag fiber, and 30 to 40 wt% of a binder are mixed to obtain a first mixture;
[0029] During the mixing process, supercritical carbon dioxide accounting for 3-4% of the mass of the first mixed material is injected into the first mixed material at a temperature of 65-75° C. and a pressure of 70-80 atm;
[0030] S2, mixing the remaining aggregate, powder, binder, potassium titanate whisker and additives to obtain a second mixture;
[0031] S3, mixing the first mixed material and the second mixed material to obtain a casting material.
[0032] Furthermore, before step S2, the potassium titanate whiskers are first subjected to chemical vapor infiltration, wherein the chemical vapor infiltration temperature is 850-900° C., the time is 1.5-3.5 h, and the gas flow rate is 0.15-0.25 m 3 / h.
[0033] Description: Chemical vapor infiltration can form a uniform coating on the surface of potassium titanate whiskers that is well compatible with the castable matrix. This coating can significantly enhance the bonding strength between the whiskers and the castable matrix. When the castable is worn, the whiskers are not easily pulled out or broken from the matrix, so that they can better play their reinforcing role and effectively improve the wear resistance of the castable; and the coating often has good chemical stability and corrosion resistance. This protective layer can prevent corrosive media from directly contacting the potassium titanate whiskers and the castable matrix, thereby reducing the probability and corrosion rate of chemical corrosion and effectively protecting the internal structure of the castable from erosion.
[0034] Furthermore, in step S2, the gas phase of the chemical vapor infiltration is one of ethane, ethylene and silane.
[0035] Note: The coating formed by the above-mentioned gas phase on the surface of potassium titanate whiskers can close some tiny pores and defects on the surface of potassium titanate whiskers, reduce its surface energy, reduce the adsorption and penetration of corrosive media on the whisker surface, and significantly enhance the interface bonding strength between the whiskers and the castable.
[0036] Compared with the existing castables, the beneficial effects of the present invention are:
[0037] (1) The present invention adds modified dust bag fibers to the castable, so that the modified dust bag fibers are interwoven in the castable to form a "net-like" structure that can effectively disperse stress. When the castable is subjected to wear stress, the fibers can bear part of the external force to prevent the expansion of cracks and the shedding of particles, thereby improving the overall wear resistance of the castable; the modified layer on the surface of the modified dust bag fibers has a certain chemical inertness, which can prevent chemical corrosive substances from contacting the inside of the castable.
[0038] (2) The present invention adds modified potassium titanate whiskers to the castable, which can fill the gaps between the corundum and spinel particles. During the wear process, the whiskers can enhance the stability of powder particles such as aggregates and powders, making them less likely to move and fall off, thereby improving the wear resistance of the castable. In the castable, the whiskers can act as a barrier to prevent the direct contact between the corrosive medium and the corundum and spinel particles, thereby reducing the possibility of the particles being corroded. In addition, the whiskers can also fill the pores in the castable, reduce the porosity, and make it difficult for the corrosive medium to diffuse and penetrate into the castable, thereby improving the chemical corrosion resistance of the castable.
[0039] (3) In the process of preparing the castable, the present invention first mixes the aggregates and powders of certain particle sizes with the modified bag fibers. Since the aspect ratio of the fibers is relatively large, mixing them with certain materials first can give them enough space and time to be evenly dispersed in these materials, thereby avoiding the agglomeration of the fibers that may occur when all are mixed at once. The surface tension of supercritical carbon dioxide is extremely small, which can reduce the surface tension between the aggregates, powders and fibers, making them easier to contact and mix with each other, further improving the mixing effect, ensuring the uniform distribution of the various components of the castable, and improving the performance consistency of the castable. Then, the potassium titanate whiskers are mixed with the remaining aggregates, powders and additives, and the whiskers can be inserted into the pores of the remaining aggregates and tightly combined with the powders, thereby utilizing the high strength and high modulus characteristics of the whiskers to enhance the performance of this part of the materials. Finally, when the two parts are mixed, since the fluidity of each part has been preliminarily optimized before, the fluidity of the entire castable is more likely to reach an ideal state, which is beneficial to ensuring the molding quality of the castable. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 is a comparison chart of the wear rate results of the castable in the experimental example 1 of the present invention;
[0041] Figure 2 It is a comparison chart of the weight loss rate results of the castable in the experimental example of the present invention;
[0042] Figure 3 is a comparison chart of the wear rate results of the investigation 2 in the experimental example of the castable of the present invention;
[0043] Figure 4 It is a comparison chart of the weight loss rate results of the castable experimental example 2 of the present invention;
[0044] Figure 5 is a comparison chart of the wear rate results of the castable experimental example 3 of the present invention;
[0045] Figure 6 It is a comparison chart of the weight loss rate results of the castable experimental example 3 of the present invention;
[0046] Figure 7 is a comparison chart of the wear rate results of the castable in Experiment 4 of the present invention;
[0047] Figure 8 It is a comparison chart of the weight loss rate results of Exploration 4 in the experimental example of the castable of the present invention. DETAILED DESCRIPTION
[0048] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.
[0049] Embodiment 1: A wear-resistant and chemical-resistant casting material, comprising, by mass percentage:
[0050] Powder: 23%;
[0051] Modified waste bag fiber: 1.5%;
[0052] Potassium titanate whiskers: 0.8%;
[0053] Pure calcium aluminate cement: 5%;
[0054] Zirconia: 2%;
[0055] Aggregate: remainder;
[0056] The aggregate is composed of corundum and spinel in a mass ratio of 2.5 to 5:1; the particle size of the corundum includes three types: 3 to 5 mm, 1 to 3 mm, and ≤1 mm, and the mass ratio of the three particle sizes is 1.8:1:2; the particle size of the spinel includes three types: 0.08 to 1 mm, 0.008 to 0.08 mm, and ≤0.008 mm, and the mass ratio of the three particle sizes is 4.5:3:3;
[0057] The powder material is composed of silicon carbide micropowder and nano-alumina in a mass ratio of 1:3, the particle size of the silicon carbide micropowder is ≤0.01mm; the particle size of the nano-alumina is ≤5nm;
[0058] The preparation method of the modified waste bag fiber is as follows:
[0059] First, the waste cloth bags are cleaned, dried and crushed to obtain cloth bag fibers with a length of 4.5 mm and a diameter of 18 um; the waste cloth bags are derived from laboratory chemical defense waste treatment bags or medical waste garbage bags;
[0060] The bag fiber was vacuum impregnated in a sucrose solution with a mass fraction of 18% at a mass ratio of 1:25 for 3.5 hours, and the vacuum degree was 3.5×10 -4 Pa; then the vacuum impregnated bag fiber was subjected to decoupled plasma nitridation treatment, wherein the radio frequency power of the decoupled plasma nitridation treatment was 2900W, the nitrogen flow rate was 235mL / min, and the treatment time was 1.5min; finally, the bag fiber after decoupled plasma nitridation treatment was vacuum impregnated in a sucrose solution with a mass fraction of 28% at a mass ratio of 1:8 for 0.8h, and the vacuum degree was 1.5×10 -4 Pa; obtain modified waste cloth bag fiber.
[0061] Example 2: A method for preparing a wear-resistant and chemical-resistant castable based on Example 1, comprising the following steps:
[0062] S1, corundum with a particle size of 3 to 5 mm and ≤ 1 mm, spinel with a particle size of 0.08 to 1 mm and 0.008 to 0.08 mm, 65 wt% of powder, modified waste bag fiber, and 35 wt% of a binder are mixed at a mixing speed of 500 r / min for 20 min to obtain a first mixture;
[0063] During the mixing process, supercritical carbon dioxide accounting for 3.5% of the mass of the first mixed material is injected into the first mixed material at a temperature of 70° C. and a pressure of 75 atm;
[0064] S2, mixing the remaining aggregate, powder, binder, potassium titanate whisker and additives at a mixing speed of 400 r / min for 20 min to obtain a second mixture;
[0065] S3. Mix the first mixed material and the second mixed material at a mixing speed of 500 r / min for 40 min to obtain a casting material.
[0066] Example 3: This example is different from Example 1 in that, by mass percentage, it includes: powder: 20%; modified waste bag fiber: 2%; potassium titanate whisker: 1%; binder: 4%; additive: 1%; aggregate: balance.
[0067] Example 4: This example is different from Example 1 in that, by mass percentage, it includes: powder: 25%; modified waste bag fiber: 1%; potassium titanate whisker: 0.2%; binder: 6%; additive: 3%; aggregate: balance.
[0068] Example 5: This example is different from Example 1 in that the aggregate consists of corundum and spinel in a mass ratio of 2.5:1.
[0069] Example 6: This example is different from Example 1 in that the aggregate consists of corundum and spinel in a mass ratio of 5:1.
[0070] Example 7: The difference between this example and Example 1 is that the particle size of the corundum includes three types: 3-5mm, 1-3mm, and ≤1mm, and the mass ratio of the three particle sizes is 1.5:1:2; the particle size of the spinel includes three types: 0.08-1mm, 0.008-0.08mm, and ≤0.008mm, and the mass ratio of the three particle sizes is 5:3:3.
[0071] Example 8: The difference between this example and Example 1 is that the particle sizes of the corundum include 3-5mm, 1-3mm, and ≤1mm, and the mass ratio of the three particle sizes is 2:1:2. The particle sizes of the spinel include 0.08-1mm, 0.008-0.08mm, and ≤0.008mm, and the mass ratio of the three particle sizes is 4:3:3.
[0072] Example 9: This example is different from Example 1 in that the powder is composed of silicon carbide micropowder and nano-alumina in a mass ratio of 1:2.
[0073] Example 10: This example is different from Example 1 in that the powder is composed of silicon carbide micropowder and nano-alumina in a mass ratio of 1:4.
[0074] Example 11: This example is different from Example 1 in that the length of the bag fiber is 3 mm and the diameter is 20 um.
[0075] Example 12: This example is different from Example 1 in that the length of the bag fiber is 6 mm and the diameter is 15 um.
[0076] Example 13: This example is different from Example 1 in that the bag fiber is vacuum impregnated in a 15% sucrose solution at a mass ratio of 1:20 for 3 h, and the vacuum degree is 3×10 -4 Pa.
[0077] Example 14: This example is different from Example 1 in that the bag fiber is vacuum impregnated in a sucrose solution with a mass fraction of 20% at a mass ratio of 1:30 for 4 hours, and the vacuum degree is 4×10 -4 Pa.
[0078] Example 15: This example is different from Example 1 in that the RF power of the decoupled plasma nitridation treatment is 2800 W, the nitrogen flow rate is 230 mL / min, and the treatment time is 1 min.
[0079] Example 16: The difference between this example and Example 1 is that the RF power of the decoupled plasma nitridation treatment is 3000 W, the nitrogen flow rate is 240 mL / min, and the treatment time is 2 min.
[0080] Example 17: This example is different from Example 1 in that the bag fiber after decoupled plasma nitridation is vacuum impregnated in a sucrose solution with a mass fraction of 25% at a mass ratio of 1:5 for 0.5 h, and the vacuum degree is 1×10 -4 Pa.
[0081] Example 18: This example is different from Example 1 in that the bag fiber after decoupled plasma nitridation is vacuum immersed in a 30% sucrose solution at a mass ratio of 1:10 for 1 hour, and the vacuum degree is 2×10 -4 Pa.
[0082] Example 19: This example is different from Example 2 in that corundum with a particle size of 3 to 5 mm and ≤ 1 mm, spinel with a particle size of 0.08 to 1 mm and 0.008 to 0.08 mm, 60 wt% of powder, modified waste cloth bag fiber, and 40 wt% of a binder are mixed.
[0083] Example 20: This example differs from Example 2 in that corundum with a particle size of 3 to 5 mm and ≤ 1 mm, spinel with a particle size of 0.08 to 1 mm and 0.008 to 0.08 mm, 70 wt% of powder, modified waste cloth bag fiber, and 30 wt% of a binder are mixed.
[0084] Example 21: This example is different from Example 2 in that, during the mixing process, supercritical carbon dioxide accounting for 3% of the mass of the first mixture is injected into the first mixture, the injection temperature is 65° C., and the pressure is 70 atm.
[0085] Example 22: This example differs from Example 2 in that, during the mixing process, supercritical carbon dioxide accounting for 4% of the mass of the first mixture is injected into the first mixture, the injection temperature is 75° C., and the pressure is 80 atm.
[0086] Example 23: This example is different from Example 2 in that, before step S2, the potassium titanate whiskers are first subjected to chemical vapor infiltration at a temperature of 875°C, a time of 2 hours, and a gas flow rate of 0.20 m 3 / h, and ethane is used in the gas phase.
[0087] Example 24: This example is different from Example 23 in that, before step S2, the potassium titanate whiskers are first subjected to chemical vapor infiltration, the chemical vapor infiltration temperature is 850°C, the time is 1.5h, and the gas flow rate is 0.15m 3 / h, ethylene is used in the gas phase.
[0088] Example 25: This example is different from Example 23 in that, before step S2, the potassium titanate whiskers are first subjected to chemical vapor infiltration at a temperature of 900°C, a time of 3.5 hours, and a gas flow rate of 0.25 m 3 / h, silane is used in the gas phase.
[0089] Experimental Example: The description of this experimental example is based on the scheme described in Example 2, and is intended to illustrate the practical application effect of the present invention.
[0090] The castables prepared in each embodiment were vibrated and cast into samples of 40mm×40mm×160mm. The samples were demolded after natural curing for 24 hours and kept at 110°C for 24 hours. Some samples were heat treated at 1100°C and 1350°C for 3 hours, respectively. Then, they were naturally cooled to room temperature for wear resistance and chemical corrosion resistance testing. The wear resistance was tested by heat treating at 1400°C for 3 hours and then performing a wear test to obtain the wear rate. The chemical corrosion resistance was tested by immersing the samples in 10% sulfuric acid and 10% sodium hydroxide for 24 hours with a weight loss rate test. The average weight loss rate of acid immersion and alkali immersion was taken as the experimental result.
[0091] 1. Investigate the influence of the ratio of each component of the castable on the wear rate and weight loss rate of the castable.
[0092] The difference between Control Example 1 and Example 1 is that no modified waste bag fiber is added;
[0093] The difference between Control Example 2 and Example 1 is that potassium titanate whiskers are not added;
[0094] Depend on Figure 1 and Figure 2 The results show that the control example 1 lacks the modified waste bag fiber, and the control example 2 lacks the potassium titanate whisker. Compared with the examples 1, 3 to 10, the wear rate and weight loss rate are significantly increased, indicating that the modified waste bag fiber prevents the expansion of cracks and the shedding of particles, and the potassium titanate whisker is indispensable for enhancing the stability of powder particles such as aggregates and powders.
[0095] By comparing Examples 1, 3 to 10, it can be seen that the wear rate and weight loss rate of the castable will be increased if the proportion of modified waste bag fibers and potassium titanate whiskers is too small or too large, the proportion of corundum in the aggregate is too small or too large, the large particle size ratio of corundum and spinel is too small or too large, and the proportion of nano-alumina in the powder is too small or too large. In comprehensive comparison, the parameter effect of Example 1 is relatively better.
[0096] 2. Investigate the influence of preparation parameters of modified waste bag fibers on the wear rate and weight loss rate of castables.
[0097] The difference between Comparative Example 3 and Example 1 is that no decoupled plasma nitridation treatment is performed;
[0098] The difference between Comparative Example 4 and Example 1 is that the second vacuum impregnation is not performed;
[0099] Depend on Figure 3 and Figure 4The results show that in the process of preparing the modified waste bag fiber, the control example 3 lacks the decoupled plasma nitriding treatment, so the surface of the bag fiber lacks the support of the hardness of the nitriding layer, and the control example 4 lacks the secondary vacuum impregnation, which reduces the active sites of the bag fiber surface and the first carbon layer. Compared with the performance of Examples 1 and 11 to 18, they are all reduced;
[0100] By comparing Examples 1 and 11 to 18, it can be seen that the wear rate and weight loss rate of the castable will increase if the aspect ratio of the bag fiber is too small or too large, the parameters of the first vacuum impregnation of the bag fiber are too small or too large, the parameters of the decoupled plasma nitriding treatment are too small or too large, and the parameters of the second vacuum impregnation are too small or too large. In comprehensive comparison, the parameter effect of Example 1 is relatively better.
[0101] 3. Investigate the influence of various parameters in the preparation of castables on the wear rate and weight loss rate of castables.
[0102] The difference between Comparative Example 5 and Example 1 is that supercritical carbon dioxide is not injected;
[0103] Depend on Figure 5 and Figure 6 As can be seen from the results, the control example 5 lacks the injection of supercritical carbon dioxide, which reduces the uniformity of the mixing of the various components compared to the examples 2 and 19 to 22 injected with supercritical carbon dioxide, and also reduces the uniform distribution of the supercritical carbon dioxide in the material after the injection, which can affect the pore formation of the castable during the hardening process, and relatively reduces the density of the castable, thereby increasing the wear rate and weight loss rate of the castable;
[0104] By comparing Examples 2 and 19 to 22, it can be seen that if the proportion of powder in the first mixture is too small or too large, and the injection parameters of supercritical carbon dioxide are too small or too large, the wear rate and weight loss rate of the castable will increase. In comprehensive comparison, the parameter effect of Example 2 is relatively better.
[0105] 4. Investigate the effect of chemical vapor infiltration of potassium titanate whiskers on the wear rate and weight loss rate of the castable.
[0106] Depend on Figure 7 and Figure 8 The results show that, compared with Example 2, Examples 23 to 25 further perform chemical vapor infiltration treatment on the potassium titanate whiskers, and form a coating on the surface of the potassium titanate whiskers, which can effectively improve the wear resistance of the castable; and the coating can prevent the corrosive medium from directly contacting the potassium titanate whiskers and the castable matrix, thereby reducing the probability and corrosion rate of chemical corrosion, and effectively protecting the internal structure of the castable from erosion, so that the corrosion resistance is also significantly improved;
[0107] By comparing Examples 23 to 25, it can be seen that if the parameters of the chemical vapor infiltration treatment are too small or too large, the reduction in the wear rate and weight loss rate will be reduced. Therefore, in comprehensive comparison, the effect of Example 23 is relatively better.
Claims
1. A wear-resistant and chemical-resistant casting material, characterized in that: In terms of mass percentage, it includes: Powder: 20-25%; Modified waste bag fiber: 1-2%; Potassium titanate whiskers: 0.5-1%; Binder: 4-6%; Additives: 1-3%; Aggregate: remainder; The aggregate is composed of corundum and spinel in a mass ratio of 2.5 to 5:1; The powder material consists of silicon carbide micropowder and nano-alumina in a mass ratio of 1:2-4.
2. A wear-resistant and chemical-resistant castable according to claim 1, characterized in that: The particle sizes of the corundum include 3-5mm, 1-3mm, and ≤1mm, and the mass ratio of the three particle sizes is 1.5-2:1:2; the particle sizes of the spinel include 0.08-1mm, 0.008-0.08mm, and ≤0.008mm, and the mass ratio of the three particle sizes is 4-5:3:
3.
3. A wear-resistant and chemical-resistant castable according to claim 1, characterized in that: The particle size of the silicon carbide powder is ≤0.01 mm; the particle size of the nano-aluminum oxide is ≤5 nm.
4. A wear-resistant and chemical-resistant castable according to claim 1, characterized in that: The preparation method of the modified waste bag fiber is as follows: First, the waste bags are cleaned, dried and crushed to obtain bag fibers with a length of 3 to 6 mm and a diameter of 15 to 20 um; The bag fiber is vacuum impregnated in a sucrose solution with a mass fraction of 15-20% at a mass ratio of 1:20-30 for 3-4 hours, and the vacuum degree is 3×10 -4 ~4×10 -4 Pa; then the vacuum impregnated bag fiber is subjected to decoupled plasma nitridation treatment, wherein the radio frequency power of the decoupled plasma nitridation treatment is 2800-3000W, the nitrogen flow rate is 230-240mL / min, and the treatment time is 1-2min; finally, the bag fiber after the decoupled plasma nitridation treatment is vacuum impregnated in a sucrose solution with a mass fraction of 25-30% at a mass ratio of 1:5-10 for 0.5-1h, and the vacuum degree is 1×10 -4 ~2×10 -4 Pa; obtain modified waste cloth bag fiber.
5. A wear-resistant and chemical-resistant castable according to claim 1, characterized in that: The additive is zirconium oxide.
6. A wear-resistant and chemical-resistant castable according to claim 1, characterized in that: The binder is pure calcium aluminate cement.
7. A method for preparing a wear-resistant and chemical-resistant castable according to any one of claims 2 to 6, characterized in that: The following steps are involved: S1, corundum with a particle size of 3 to 5 mm and ≤ 1 mm, spinel with a particle size of 0.08 to 1 mm and 0.008 to 0.08 mm, 60 to 70 wt% of powder, modified waste bag fiber, and 30 to 40 wt% of a binder are mixed to obtain a first mixture; During the mixing process, supercritical carbon dioxide accounting for 3-4% of the mass of the first mixed material is injected into the first mixed material at a temperature of 65-75° C. and a pressure of 70-80 atm; S2, mixing the remaining aggregate, powder, binder, potassium titanate whisker and additives to obtain a second mixture; S3, mixing the first mixed material and the second mixed material to obtain a casting material.
8. The method for preparing a wear-resistant and chemical-resistant castable according to claim 7, characterized in that: Before step S2, the potassium titanate whiskers are first subjected to chemical vapor infiltration at a temperature of 850 to 900° C., a time of 1.5 to 3.5 hours, and a gas flow rate of 0.15 to 0.25 m 3 / h.
9. The method for preparing a wear-resistant and chemical-resistant castable according to claim 7, characterized in that: In step S2, the gas phase of the chemical vapor infiltration is one of ethane, ethylene and silane.